Analisis Kejahatan Transnasional melalui Aktivitas Money Laundering dalam Illegal Wildlife Trade di India - Natasha, Queen Nindya (Department of International Relations, Brawijaya University, 2022)
This article aims to describe the relation between Money Laundering and illegal wildlife trade, with the case study focused on India. Money laundering operations in this article are part of a transnational crime act to disguise the illegal profits of Illegal Wildlife Trade (IWT) and are carried out through the stages of placement, layering, and integration. The findings of this paper are (1) identify the scope of the spread of money laundering within global, national, and regional levels and the impacts; (2) acknowledge the implementation of the model of cooperation which has succeeded in identifying the political conditions in India which are identified as weak states in applying the law & also the model of operation that used the Strategic/Risk Management Model as the TOC entity strategy to minimize the legal risk; and (3) finding methods to address and policy recommendations at various levels with the role of the Financial Action Task Force (FATF) at the global level, Anti-Money Laundering (AML) at the regional level in the South Asian region, and the Prevention of Money Laundering Act (PMLA) which was established in 2012 as a preventive measure for India to eradicate money laundering at the national level.Keywords: Money Laundering; Illegal Wildlife Trade; Transnational Organized Crime